Public roads (U.S. G.P.O., 1918)
"Established in 1918, Public Roads is the premier quarterly magazine of the Federal Highway Administration (FHWA). Each issue covers the latest in highway research and development, innovation and technology, and program advancements that benefit the Nation and create safer, more resilient roadways and structures. Public Roads emphasizes the continuing commitment of FHWA to be an international leader in promoting highway research and technology transfer for transportation professionals across the Nation and around the world. The more than 100-year-old magazine explores advances and innovations in highway, traffic, and bridge research and technology; critical national transportation issues; program advancement and achievements of FHWA and others in the highway community; and timely subjects of interest to industry professionals. For almost 80 years, Public Roads was exclusively an in-house research journal for engineers, scientists, and economists. However, in the summer of 1993, Public Roads broadened its scope to represent all areas of FHWA while offering articles that appealed to a wider audience. The expanded audience now includes international, national, State, local, and Tribal transportation officials; members of highway-related professional societies and associations; researchers at technical libraries and technology transfer centers; professors and students of engineering and traffic management; members of pertinent congressional committees; and others interested in highway research and technology and FHWA policies and programs." - Federal Highway Administration website.